Factors That Increase The Risk of A Mother Giving Birth to A Stunting Toddler - Sitorus, Rotua Sumihar; Suprianto, Suprianto; Herlina, Herlina (Jurnal Keperawatan Priority, 2024)
Stunting is a condition where linear growth is disturbed so that the body height is not normal, also known as being short or dwarf in comparison to the standard age. This matter is caused by nutrition and health in the poor pre- and post-natal period. An educated and knowledgeable mother has a significant role in overcoming, managing, and organizing family resources to meet nutritional needs. The study was directed at analyzing factors that increase the risk of mothers giving birth to stunted toddlers in work areas at the Public Health Center Namorambe. The study uses a descriptive-analytical approach using a cross-sectional model, where data collection is conducted in a single instance.Thirty mothers were studied as study subjects with toddlers ages 0–60 months with stunting conditions and living in the work area of the Public Health Center Namorambe. The study results show that the possibility of mothers giving birth to stunted toddlers is affected by their knowledge, attitudes, and actions.